U-shaped association between sleep duration and frailty in Chinese older adults: a cross-sectional study - Yanliqing Song; Haoqiang Liu; Kenan Gu; Yue Liu (Frontiers in Public Health)
ObjectiveAs the population ages, understanding the association between sleep patterns and physical frailty in older adults is crucial for formulating effective health interventions. This study aimed to explore the relationship among nap time, nighttime sleep duration, and physical frailty in older Chinese individuals; establish recommended sleep times; and provide a scientific and reasonable basis for the prevention and management of frailty in older adults.MethodsOn the basis of the 2020 China Health and Retirement Longitudinal Study database, demographic information, health data, and lifestyle information of the research subjects were obtained. A total of 5,761 survey participants were included, and logistic regression and restricted cubic splines were used to explore the association between sleep duration and frailty.ResultsIn our cross-sectional analysis, the duration of napping in older adults did not show a significant correlation with frailty. The optimal nighttime sleep interval for older adults was 7–8 h, and the maximum health benefit was achieved when nighttime sleep reached 7.5 h. Compared with older adults in China who slept 6–8 h at night, those with a sleep duration of <6 h (OR = 1.58, 95% CI: 1.36–1.82) were more likely to be frail. After adjusting for all covariates such as smoking, multimorbidity, self-rated health, social events, education level, and frequency of physical activity, we found no interaction between gender and age concerning sleep duration.ConclusionThe potential correlation between nighttime sleep duration and frailty in older adults is basically U-shaped. Older Chinese adults with a moderate nighttime sleep duration of 7–8 h exhibited the lowest likelihood of frailty than their counterparts. The duration of napping is not related to the likelihood of frailty in older people. Thus, the importance of sufficient nighttime sleep for the health of older adults must be emphasized.